Binuclear meta‐xylyl‐linked Ag(I)‐N‐heterocyclic carbene complexes of N‐alkyl/aryl‐alkyl‐substituted bis‐benzimidazolium salts: synthesis, crystal structures and in vitro anticancer studies. (27th March 2013) - Haque, Rosenani A.; Iqbal, Muhammad Adnan; Budagumpi, Srinivasa; Khadeer Ahamed, Mohamed B.; Abdul Majid, Amin M. S.; Hasanudin, Noorhafizah
Abstract : Salts of meta ‐xylyl‐linked N ‐ethyl/ n ‐butyl/benzyl‐substituted bis‐benzimidazolium having hexafluorophosphate counterions have been synthesized. The corresponding binuclear Ag(I)‐ N ‐heterocyclic carbene complexes were prepared by the reaction of Ag2 O. The N ‐heterocyclic carbene (NHC) ligand precursor 7 and Ag(I)–NHC complexes 10 and 11 have been structurally characterized by single‐crystal X‐ray diffraction technique. All of the reported compounds have been tested for their anticancer activity using human colorectal (HCT 116) cancer cell lines. Sterically varied benzimidazolium salts displayed significant activity against HCT 116 cell line, yielding IC50 values in the range 0.1–19.4 µm, while Ag(I)–carbene complexes showed exceptionally good activity (0.2–1.3 µm ) against tested cancer cell lines. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Meta ‐xylyl‐bridged symmetrically substituted Ag(I)‐N‐heterocyclic carbene complexes were prepared and have been tested for their anticancer activity using human colorectal (HCT 116) cancer cell lines. Ag(I)‐carbene complexes showed exceptionally good activity (0.2‐1.3 µM) against tested cancer cell lines.